A Tie-Over Dressing Using a Silicone Tube to Graft Deep Wounds - Cem Inan Bektas; Yuksel Kankaya; Kadri Ozer; Ruser Baris; Ozlem Colak Aslan; Ugur Kocer (Archives of Plastic Surgery, 2013)
Background The most common cause of skin graft failure is the collection of blood or serous fluid underneath the graft. In our study, we describe the use of silicone tube for tie-over dressing to secure the skin graft margins with the aim of decreasing loss of the skin graft, particularly in grafting of deep wounds. Methods Between March 2008 and July 2011, we used this technique in 17 patients with skin defects with depths ranging from 3.5 to 8 mm (mean, 5.5 mm). First, the skin graft was sutured with 3/0 silk suture material from its corners. Then, a silicone round drain tube was sutured with 3/0 absorbable polyglactin 910 over the margins of the graft. Finally, long silk threads were tied over the bolus dressing, and the tie-over dressing was completed in the usual fashion. Results The mean follow-up was 7 months (range, 2-10 months) in the outpatient clinic. Graft loss on the graft margins due to hematoma or seroma was not developed. The results of adhesion between the graft and wound bed peripherally was excellent. Conclusions In our study, we suggest that use of a silicone tube for additional pressure on the edges of skin grafts in case of reconstruction of deep skin defects.